2018
DOI: 10.1111/sms.13077
|View full text |Cite
|
Sign up to set email alerts
|

Strength and cardiometabolic risk in young adults: The mediator role of aerobic fitness and waist circumference

Abstract: The aim of this study was to analyze the mediation role of cardiorespiratory fitness and waist circumference in the association between muscular strength and cardiometabolic risk. A cross-sectional study involved first-year college students (n = 370) from a Spanish public university was performed. We measured weight, height, waist circumference, blood pressure, biochemical variables, maximum handgrip strength assessment, and cardiorespiratory fitness. We calculated handgrip dynamometry/weight and a previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 35 publications
4
23
0
Order By: Relevance
“…Recent studies have shown that grip strength and other muscle strengths as well as various strength trainings have positive effects on cardiometabolic outcomes [33,34,35,36]. Therefore, in this study, improvement in the strength of the lower extremities (measured by the wall sit test in the exercise group after the intervention) could be expected to have a positive effect on cardiometabolic outcomes, in addition to the effect of weight control in obese children and adolescents.…”
Section: Discussionmentioning
confidence: 87%
“…Recent studies have shown that grip strength and other muscle strengths as well as various strength trainings have positive effects on cardiometabolic outcomes [33,34,35,36]. Therefore, in this study, improvement in the strength of the lower extremities (measured by the wall sit test in the exercise group after the intervention) could be expected to have a positive effect on cardiometabolic outcomes, in addition to the effect of weight control in obese children and adolescents.…”
Section: Discussionmentioning
confidence: 87%
“…The participants were selected from three primary schools in Shanghai (China). A sampling of schools was stratified according to physical fitness with three levels, with the first quartile being the lowest, followed by second and third quartiles, and the highest being the fourth quartile, as described and used in previous studies ( 32 , 33 ). The current three schools were chosen for their representativeness of each level, considering the accessibility to our research team and the availability of the teachers to assist with logistics.…”
Section: Methodsmentioning
confidence: 99%
“…It has been documented, for example, that physical inactivity substantially increases the risk for developing major chronic diseases, including cardiovascular disease, type 2 diabetes, or certain types of cancer . The degree of cardiorespiratory fitness (CRF) is commonly used as an objective and reproducible marker of physical activity habits and regarded as an independent predictor of mortality—much stronger than other well‐recognized risk factors, such as smoking or obesity . Public health guidelines recommend that adults should accumulate a minimum volume of 150 minutes of moderate physical activity or 75 minutes of vigorous aerobic exercise per week in order to maintain and/or improve CRF and other health outcomes …”
Section: Introductionmentioning
confidence: 99%